Enhancing functionalities in nanocomposites for effective dye removal from wastewater: isothermal, kinetic and thermodynamic aspects - Javed, Ifrah; Hanif, Muhammad Asif; Rashid, Umer; Nadeem, Farwa; Alharthi, Fahad A.; Kazerooni, Elham Ahmed (Multidisciplinary Digital Publishing Institute, 2022)
The adsorption process combined with electrocoagulation is a highly effective technique for dye removal. Calcinized and non-calcinized composites based on bentonite and sodium zeolite were prepared for adsorptive removal of Foron EBL blue, Terasil brown 2RFL, Torque blue PG, and Orange P3R dyes. Factors affecting the adsorption process, such as contact time, initial dye concentration, and temperature, were also explored in this study. Equilibrium data of natural clay composites was explained by Freundlich, Langmuir, Dubinin Radushkevich isotherm, Harkin Jura, and Temkin isothermal models. Harkin Jura isotherm model best fitted on the adsorption mechanism compared to Langmuir and Temkin isotherm model. Morphology of clay-based adsorbents and functional group arrangement were investigated by scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The calcinized nano-composite material exhibited better adsorption capacity than non-calcinized nano-composite and could be employed as a low-cost alternative for dye removal.